Nutritional management of phenylalanine hydroxylase (PAH) deficiency in pediatric patients in Canada: a survey of dietitians’ current practices - Yuskiv, Nataliya; Potter, Beth K; Stockler, Sylvia; Ueda, Keiko; Giezen, Alette; Cheng, Barbara; Langley, Erica; Ratko, Suzanne; Austin, Valerie; Chapman, Maggie; Chakraborty, Pranesh; Collet, Jean P; et al. (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background Phenylalanine hydroxylase (PAH) deficiency is one of 31 targeted inherited metabolic diseases (IMD) for the Canadian Inherited Metabolic Diseases Research Network (CIMDRN). Early diagnosis and initiation of treatment through newborn screening has gradually shifted treatment goals from the prevention of disabling complications to the optimization of long term outcomes. However, clinical evidence demonstrates that subtle suboptimal neurocognitive outcomes are present in the early and continuously diet-treated population with PAH deficiency. This may be attributed to variation in blood phenylalanine levels to outside treatment range and this, in turn, is possibly due to a combination of factors; disease severity, dietary noncompliance and differences in practice related to the management of PAH deficiency. One of CIMDRN’s goals is to understand current practices in the diagnosis and management of PAH deficiency in the pediatric population, from the perspective of both health care providers and patients/families. Objectives We investigated Canadian metabolic dietitians’ perspectives on the nutritional management of children with PAH deficiency, awareness of recently published North American treatment and nutritional guidelines in relation to PAH deficiency, and nutritional care practices within and outside these guidelines. Methods We invited 33 dietitians to participate in a survey, to ascertain their use of recently published guidelines and their practices in relation to the nutritional care of pediatric patients with PAH deficiency. Results We received 19 responses (59% response rate). All participants reported awareness of published guidelines for managing PAH deficiency. To classify disease severity, 89% of dietitians reported using pre-treatment blood phenylalanine (Phe) levels, alone or in combination with other factors. 74% of dietitians reported using blood Phe levels ≥360 μmol/L (6 mg/dL) as the criterion for initiating a Phe-restricted diet. All respondents considered 120-360 μmol/L (2–6 mg/dL) as the optimal treatment range for blood Phe in children 0–9 years old, but there was less agreement on blood Phe targets for older children. Most dietitians reported similar approaches to diet assessment and counseling: monitoring growth trends, use of 3 day diet records for intake analysis, individualization of diet goals, counseling patients to count grams of dietary natural protein or milligrams of dietary Phe, and monitoring blood Phe, tyrosine and ferritin. Conclusion While Canadian dietitians’ practices in managing pediatric PAH deficiency are generally aligned with those of the American College of Medical Genetics and Genomics (ACMG), and with the associated treatment and nutritional guidelines from Genetic Metabolic Dietitians International (GMDI), variation in many aspects of care reflects ongoing uncertainty and a need for robust evidence.